The Effect of Using English Animation Videos on Students' Speaking Ability - Dinda Nabila Junita; Rabindra Dev Prasad (Cahaya Ilmu Cendekia Publisher, 2024)
This research aims to collect empirical data regarding the effectiveness of using English animated videos in improving the speaking skills of eighth grade students at SMPN 9 South Tangerang. The research method used is quantitative with a quasi-experimental approach. The population of this research was class VIII students at SMPN 9 South Tangerang. A total of 60 students were selected as samples using purposive sampling techniques and divided into two groups, namely the experimental group and the control group. The instrument used was an oral test given before and after treatment. Pre-test and post-test data were analyzed using the t-test. The pre-test results showed that the average score of the experimental group was slightly higher than the control group, while the post-test results showed a significant difference, with the experimental group's score being much higher than the control group. The research results show a significance value (p) of 0.000 with a confidence level of α = 0.05, which shows that the use of English animated videos is effective in improving students' speaking skills in eighth grade at SMPN 9 South Tangerang.